Estudo do escoamento turbulento de fluido supercrítico em tubo capilar aplicado à produção de nanopartículas - Almeida, Regiani Aparecida de (2013)
Processes that employ Supercritical fluid as the SAS technique or Supercritical Antisolvent using Supercritical CO2 as Antisolvent to the precipitation of particles, in micro and nanoscales, allow to process a wide variety of high quality products from the pharmaceutical and food industry. They have advantages over other recrystallization techniques to produce particles of small size with spherical shapes as precipitation heat sensitive compounds, which are desirable in many applications and easy to separate of the organic solvent. However, the guarantee of obtaining particles with beneficial biophysical characteristics and shapes is related to a combination of operating process parameters of each solute-organic solvent system under consideration. This combination of parameters is a great defiance in the process control. It is known that by varying the antisolvent and solution flow rates, operating pressure and temperature, the chamber geometry and capillary injection tube is possible to vary properties such as density and solubility in supercritical conditions of the mixture. Thus, it is feasible to enhance the control over the precipitated particles, size and shape. Indeed, the mechanisms of precipitation using supercritical fluids have not been systematically studied and a little is known about the fluid dynamic behavior of supercritical mixture and its effects on the particles, size and shape. This work proposes a study about flow dynamics in supercritical conditions, in a SAS - precipitation chamber. The research is based on the solution of a mathematical model involving the variables that describe the flow in such conditions. The system of partial and differential equations that model the process is numerically solved by employing the ANSYS FLUENT commercial code. Four cases of chambers with dimensions and different injection systems were chosen from the literature: two two-dimensional and two three-dimensional cases. It was analyzed how the variations, in the operating conditions (geometry of the chamber, pressure and flow rates of antisolvent), correlate to the trends of experimental particle size and morphology as reported in the literature. A comparison among the results has pointed out that two and three dimensional approaches allow the 2D to answer questions about the influence of the process parameters on the quality of shaped particles, with few computational efforts. However, the 3D approach has shown more complex patterns, the influence of the parameters is better detailed in this case, and this method should be selected when possible. It was observed that the fluid flows faster along the bottom wall with a greater velocity of gradients, in the shorter chambers length, and this may explain the formation of larger particles clusters experimentally observed. The tracking of the jet boundary allowed locating the possible regions of particle nucleation. This was corroborated by the supersaturation profiles that revealed very distinct nucleation regions in the precipitation chamber.